Stimulans 1997. - de Bethune, Emmanuel; vzw Stimulans (Stad Kortrijk, 1997)
Huyghe, Thomas ; Bentein, Yannik ; Nolf, Heidi ; Bruneel, David ; Debrabandere, Kurt ; Denauw, Geert ; Denys, Christophe ; Houttekiet, Ben ; Rigole, Dirk ; Van Hasten, Steven ; Samyn, Els ; Verbeke, Nele ; Vercouttere, Terence ; Vercaemer, Stephan ; Swaelens, Magali ; Vanpoucke, Joost ; Vindevogel, Tine ; Boucquet, Lieven ; Verduyn, Claude
biografie
Stimulans 1997, Kortrijk, 1997
Nederlands
boek